2019
DOI: 10.1080/15548627.2019.1643184
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induction by the pathogen receptor NECTIN4 and sustained autophagy contribute to peste des petits ruminants virus infectivity

Abstract: Macroautophagy/autophagy is an essential cellular response in the fight against intracellular pathogens. Although some viruses can escape from or utilize autophagy to ensure their own replication, the responses of autophagy pathways to viral invasion remain poorly documented. Here, we show that peste des petits ruminants virus (PPRV) infection induces successive autophagic signalling in host cells via distinct and uncoupled molecular pathways. Immediately upon invasion, PPRV induced a first transient wave of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 81 publications
(156 reference statements)
0
31
0
Order By: Relevance
“…Yang et al found that using microRNA to inhibit the expression of IRGM/Irgm1 can directly or indirectly attenuate the autophagy of macrophages induced by the peste des petits ruminants virus (46). Hence, IRGM/Irgm1 is known as an autophagy-related protein and has been widely studied in inflammation and tumor diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al found that using microRNA to inhibit the expression of IRGM/Irgm1 can directly or indirectly attenuate the autophagy of macrophages induced by the peste des petits ruminants virus (46). Hence, IRGM/Irgm1 is known as an autophagy-related protein and has been widely studied in inflammation and tumor diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Virus stock was prepared by collecting the infected Vero cell supernatant when cytopathic effect (CPE) affected about 80% of the cells. The virus was harvested by three cycles of freezing and thawing and stored at −80 ‱ C and purified by banding on sucrose gradient (33). The purified virus titers were estimated by estimating 50% tissue culture infective doses (TCID 50 ) using Vero cells in 96-well microtiter plate.…”
Section: Cells and Virusmentioning
confidence: 99%
“…All these data highlight that mTOR is a key regulator of immune function impacting the immune cells maturation and differentiation and serving as a link between regulation of metabolism and function and activity of the cells of the immune system among others (Patsoukis et al 2017 ). In sum, the mTOR-based modulatory and interconnected molecular events of essential and specialized host mechanisms in response to pathogen infections seems to be crucial for the control of infection and its therapeutic or prophylactic targeting might have significant clinical implications (Yang et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Viruses have different targeting strategies between vertebrates and arthropod vectors and some like dengue virus serotype-2 (DENV-2) and ZIKA viruses obtain relevant benefits of arthropod TOR autophagy inhibition (Brackney et al 2020 ; Le Sage et al 2016 ; Patel and Hardy 2012 ). In this sense, the inhibition of the PI3K-AKT-mTOR pathway affects the autophagic reaction induced by pathogen infections (Yang et al 2020 ). Therefore, autophagy and mTOR have a close relationship acting as a multi-use bridge in pathogen infections and host cells, especially taking into account its immune signaling involvement on innate and adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%